Inventory Control Analysis Using Economic Order Quantity (EOQ) in the Pekalongan Batik Industry - Winati, Famila Dwi; Indarwati, Titi (BIOMEJ, 2023)
One of the economic sectors that is able to provide a significant increase in Indonesia's economic growth is MSMEs, which operate in the creative industry sector. On the other hand, MSMEs are a business sector that is often faced with uncertainty. One of the batik MSMEs in Pekalongan was forced to face post-disruption effects such as a pandemic, which had an impact on decreasing demand and increasing supply. Therefore, strategies are needed to remain competitive in the market, one of which is inventory management. The EOQ model is used in this research to minimize raw material inventory costs by determining the economical order quantity (Q) in one of the Pekalongan batik industries. The results of this research provide a concrete reference for MSMEs to plan their supply of fabric raw materials, starting from determining order frequency, reorder points, and safety stock. The optimal order quantity for MSME raw materials is 10,189 meters, with an order frequency of 35 times in the planning horizon. The safety stock level that must be prepared is 3,988 meters, and the reorder point is 6,362 meters to meet demand during lead time. Through the proposed inventory planning, MSMEs can save inventory costs and allocate resources for other purposes.